2021
DOI: 10.17239/l1esll-2021.21.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Fluency and its relationship with typology, exposure and lexical retrieval in bilingual Persian-Swedish children’s writing

Abstract: Bilingual literacy not only supports academic success it also contributes to bilingual children's development of identity. However, not all contexts allow children to develop their writing fluency in their first language (L1) to the same degree as in their school language, their second language (L2). Few studies have explored bilingual children's writing fluency in two languages and most studies to date have focussed on Latin scripts, in particular English. The present paper fills this gap by exploring writing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…It could also result in the production of shorter texts as they struggle to find words to convey their message and they may feel inclined to produce shorter texts. The results of this study are in line with a previous study on the same group of participants in which a significant relationship was found between lexical retrieval and writing fluency in children's L1, but not in their L2 (Johansson & Lindgren, 2021). Johansson and Lindgren (2021) described how the participants' writing in L1 appeared to function more like an L2 and was more consistent with findings from L2 studies.…”
Section: The Effects Of Reading Linguistic and Cognitive Skills On Fl...supporting
confidence: 91%
See 3 more Smart Citations
“…It could also result in the production of shorter texts as they struggle to find words to convey their message and they may feel inclined to produce shorter texts. The results of this study are in line with a previous study on the same group of participants in which a significant relationship was found between lexical retrieval and writing fluency in children's L1, but not in their L2 (Johansson & Lindgren, 2021). Johansson and Lindgren (2021) described how the participants' writing in L1 appeared to function more like an L2 and was more consistent with findings from L2 studies.…”
Section: The Effects Of Reading Linguistic and Cognitive Skills On Fl...supporting
confidence: 91%
“…Writers appear to have higher writing fluency in their L1 than their L2 (Miller et al, 2008;Schoonen et al, 2009), probably as a result of more experience. This assumption is confirmed by a recent study by Johansson and Lindgren (2021) suggesting that Persian-Swedish bilingual children in years 4 to 9 had higher writing fluency in their L2 (Swedish) than their L1 (Persian). These researchers reported that the children were more used to reading and possibly writing in their L2 (Swedish) than their L1 (Persian).…”
Section: Bilingual Children's Writing Fluencysupporting
confidence: 78%
See 2 more Smart Citations
“…One of the most critical factors in creating written texts is the mastery of discourse analysis because analysis has an important influence on drawing attention to the art of language, which puts the user's knowledge of phonological, grammatical, and lexical resources into action every time the language user achieves successful communication (Johansson & Lindgren, 2021). Moreover, there are four basic skills in English, including; listening, reading, speaking, that is not easy to master for students.…”
Section: Introductionmentioning
confidence: 99%